Changes of male and female cardiovascular mortality in the Russian Federation over 2013-2022 - V. Yu. Semenov; I. V. Samorodskaya (Российский кардиологический журнал)
Aim. To analyze the changes of standardized male and female cardiovascular mortality rates over 2013-2022.Material and methods. Rosstat data on the mean annual population size and death rate according to C51 form "Deaths by sex and one-year age groups" based on the "Brief nomenclature of causes of death of Rosstat" in 2013-2022 were used. Standardized mortality rates (SMR) were calculated using software using the European population standard by the direct standardization.Results. In the Russian Federation, a decrease in the SMR for cardiovascular diseases (CVDs), coronary artery disease (CAD), alcoholic cardiomyopathy (ACM) and acute cerebrovascular accident (CVA) was registered among men and women with a slight increase in the SMR during the COVID-19 pandemic. The decrease in the SMR for myocardial infarction (MI) was 35%. Mortality from CVDs in men is 2 times higher than in women, from MI — 2,5 times, from other acute forms of CAD — 3 times, from ACM — 4 times. In addition, 40% of the SMR in men and women are chronic CAD forms. The total proportion of MI and CVA, which are the target of regional programs to reduce cardiovascular mortality, does not exceed 20%.Conclusion. The revealed almost twofold excess of cardiovascular mortality in men compared to women indicates the need for more active preventive work among the male population of the country. When extending regional programs to combat cardiovascular diseases, it should be taken into account that 80% of cardiovascular mortality rate is due to causes other than MI and stroke.